Customer Movement from Traditional Physical Service Encounters to Self-Service Technologies: An Approach to ‘Service Performance’ and ‘User Convenience’ - Badra Sandamali Galdolage (New Visions in Science and Technology Vol. 5, 2021)
Improvements in technologies provide incredible service performance that customers have never been experienced at traditional service encounters managed by service staff. Further, Self Service Technologies (SSTs) presents remarkable customer convenience by allowing them to perform various service transactions at their fingertips. However, very few studies focused on understanding SSTs profoundly. Thus, this research aims to explore ‘performance’ and ‘convenience’ related to SSTs in detail which cause customer movement from traditional physical service encounters to SSTs. Based on the qualitative research approach, semi-structured interviews were conducted with 25 SST users, and data were analyzed using the thematic analysis approach. The study found eight performance features: ‘usefulness, speed, efficiency, consistency, cost-effectiveness, user-friendliness, reliability, trialability’ and three convenience features, ‘locational convenience, time convenience and physical exertion’ as important in customer choice of SSTs. This study fills the gap in the literature by discussing two crucial matters in customer choice of SSTs in detail. It opens theoretical lenses to understand the significance of self-service technologies to customers from its performance and convenience perspectives. It provides useful insights for SST service providers that can be incorporated into their SSTs in designing and delivering a high-quality service that matches the customers’ expectations.